The Influence of Exchange Rate, World Oil Price, and BI Rate on Airline Companie’s Return in Indonesian Stock Market - Yonatan Alvin Stefan; Robiyanto Robiyanto (Universitas Pendidikan Ganesha, 2019)
In an effort to support the economic growth of Indonesia, an infrastructure development is carried out to achieve the national development. It brings positive influences on transportation companies in Indonesia. Many companies list their shares to Indonesia Stock Exchange, including PT. Garuda Indonesia (Persero) Tbk (IDX code: GIAA) and PT. AirAsia Indonesia Tbk (IDX code: CMPP), aiming to have additional capital sources. The two companies can be such a reference for investors to make investments, but they still need to consider the macro factors attached. This study examines the influende of exchange rate, world oil price, and Bank Indonesia (BI) rates on the GIAA and CMPP stock returns. The analysis technique used was Generalize Autoregressive Conditional Heteroscedasticity (GARCH) and daily data starting from their IPO to February 28th, 2019. The results showed that the exchange rate negatively affected the GIAA and CMPP stock returns, while the world oil prices only negatively affected the CMPP stock return, and the BI rates only negatively affected the GIAA stock return. In general, the investors are suggested not to buy the GIAA and CMPP shares when the IDR exchange rate weakens against the US dollar exchange rate.